Beyond victimhood, towards citizenship: (Re)conceptualising campus climate for LGBTQ+ university students in the Australian context. Issue 7 (10th November 2022) - Sharp, Megan; Shannon, Barrie; Grant, Ruby
ABSTRACT: Research which attends to LGBTQ+ students' experiences in Higher Education (HE) asserts that they are more likely to be targets of physical, verbal and symbolic violence than non-LGBTQ+ students, have poorer mental health and wellbeing, and report university settings and systems as generally exclusionary and unsafe. The Australian body of research concerning LGBTQ+ people in HE is developing but remains sparse, relying largely on concepts and empirical evidence from the United States and United Kingdom. While important to understanding LGBTQ+ exclusion in HE as a global phenomenon, we argue that concepts of 'campus climate' and 'harm' are under-theorised in Australian literature. This obscures a consistent and meaningful analysis of LGBTQ+ student lived experience. As an extension, a focus on LGBTQ+ students as 'at-risk' means understandings of the everydayness of student life and education remain limited. We suggest that by attending to the particularity of Australian HE settings, we might open our thinking to the possibilities of a global research agenda which sets out to account for similarities and differences among diverse populations while attending to LGBTQ+ students as social citizens. Ultimately, institutional frameworks that deny LGBTQ+ people full participation in university life can be critiqued meaningfully, leading to an evidence-base of equity principles, which can be implemented for LGBTQ+ students in Australia and abroad.